Sustainability transitions through electric vehicles: The relevance of network externalities - Berg, Moritz; Holtbrügge, Dirk (Taylor and Francis, 2023)
Private transport is a main cause of global warming. One attempt to reduce its ecological footprint is the replacement of internal combustion engine cars through Electric Vehicles (EVs). Their wider adoption by costumers mainly depends on the access to efficient charging stations. The relationship between EVs and charging stations can be regarded as a specific case of two-sided markets or network externalities where both sides of the market affect each other. Based on data for the period 2010-2021, we analyze whether there is a correlation between charging stations and the demand for EVs. The study shows that the increase in public charging stations has a positive effect on the demand for EVs. This effect is found worldwide and-with some country-specific variations-for the four countries China, Germany, Norway and the USA. The results contribute to the broad literature on indirect network effects and two-sided markets in relation to early technology adoption. We derive strategy implications for firms and implications for economic policy.
CRIS-Team Scopus Importer:2023-12-01